Adaptation of an Occupational Stress Index (Journal of Life and Earth Science, 2011)
Key words: Occupational stress index (OSI); reliability; test-retest method; correlation of coefficientDOI: 10.3329/jles.v3i0.7448 J. Life Earth Sci., Vols. 3-4: 55-57, 2009